Loss of Deacetylation Enzymes Hdac6 and Sirt2 Promotes Acetylation of Cytoplasmic Tubulin, but Suppresses Axonemal Acetylation in Zebrafish Cilia - Łysyganicz, Paweł K.; Pooranachandran, Niedharsan; Liu, Xinming; Adamson, Kathryn I.; Zielonka, Katarzyna; Elworthy, Stone; van Eeden, Fredericus J.; Grierson, Andrew J.; Malicki, Jarema J. (Frontiers in Cell and Developmental Biology, 2021)
Cilia are evolutionarily highly conserved organelles with important functions in many organs. The extracellular component of the cilium protruding from the plasma membrane comprises an axoneme composed of microtubule doublets, arranged in a 9+0 conformation in primary cilia or 9+2 in motile cilia. These microtubules facilitate transport of intraflagellar cargoes along the axoneme. They also provide structural stability to the cilium, which may play an important role in sensory cilia, where signals are received from the movement of extracellular fluid. Post-translational modification of microtubules in cilia is a well-studied phenomenon, and acetylation on lysine 40 (K40) of alpha tubulin is prominent in cilia. It is believed that this modification contributes to the stabilisation of cilia. Two classes of enzymes, histone acetyltransferases and histone deacetylases, mediate regulation of tubulin acetylation. Here we use a genetic approach, immunocytochemistry and behavioural tests to investigate the function of tubulin deacetylases in cilia in a zebrafish model. By mutating three histone deacetylase genes (Sirt2, Hdac6 and Hdac10), we identify an unforeseen role for Hdac6 and Sirt2 in cilia. As expected, mutation of these genes leads to increased acetylation of cytoplasmic tubulin, however, surprisingly it caused decreased tubulin acetylation in cilia in the developing eye, ear, brain and kidney. Cilia in the ear and eye showed elevated levels of mono-glycylated tubulin suggesting a compensatory mechanism. These changes did not affect the length or morphology of cilia, however, functional defects in balance was observed, suggesting that the level of tubulin acetylation may affect function of the cilium.